Overview of Brazilian industrial radiography accidents with cutaneous radiation syndrome (Brazilian Journal of Radiation Sciences, 2018)
Many of industrial radiological accidents are related to industrial gamma radiography, which makes this practice the highest potential risk for human health. More than 80 radiological accidents occurred in the world that includes 6 Brazilian accidents with Cutaneous Radiation Syndrome. From 1985 to 2000 five Brazilian accidents happened with 192Ir and one with 60Co radioactives sources. Nineteen members of the public and 8 radiographers were involved. All of them suffered severe hands and fingers injuries. Brazilian accidents were analyzed showing the main causes, the consequences for workers, estimated radiation doses and main lessons learned. This paper describes a detailed summary of each radiological accident in industrial gamma radiography occurred in Brazil.